Disparities in Health and Economic Burden of Cancer Attributable to Suboptimal Diet in the United States. (29th May 2020) - Wang, Lu; Du, Mengxi; Cudhea, Frederick; Griecci, Christina; Eom, Heesun; Michaud, Dominique; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Suboptimal diet contributes to substantial health disparities among low-income and racial and ethnic minorities, but influences on cancer disparities are not well established. We quantified the health and economic burdens of cancer attributable to suboptimal diet among US adults overall and in key demographic subgroups. Methods: Using a probabilistic cohort state transition model, we incorporated national representative demographics and dietary data, national cancer incidence and cancer survival, diet-cancer etiologic associations, and cancer-related healthcare costs to estimate new cancer cases, cancer deaths, and cancer costs attributable to suboptimal intakes of 7 dietary factors (fruits, vegetables, dairy, whole grains, processed meats, red meats, sugar sweetened beverages) among US adults aged 20 + years over their lifetime. Uncertainties in inputs were incorporated using probabilistic sensitivity analyses in 1000 simulations. Results: Suboptimal intakes of these 7 dietary factors were estimated to jointly cause 1.76 (95% UI: 1.69–1.81) million new cancer cases, representing 4.6% (4.5–4.8%) of total cases of these cancers, 1.04 (1.00–1.08) million cancer death, and $215B (206–223) cancer-related healthcare costs in US adults over their lifetime. The top 3 diet-attributable cancers were colorectal (n = 824, 000 new cases, 17% of the total), oral cavity and pharynx (n = 204, 000, 8.4%), and endometrial cancer (n = 175, 000, 5.8%). Among subgroups, diet-attributable new cancer cases per 100, 000 population were 16% higher for men (805 [777–843]) than women, 20% higher for non-Hispanic blacks (939 [901–954]) than non-Hispanic white, 12% higher for below college educated (771[727–817]) than college graduates, 14% higher for lower income individuals (income-to-poverty ratio < 1.3: 810 [771–839]) and 21% higher for SNAP participants (872 [830–920]) compared to high income individuals. Similar patterns were observed for diet-associated cancer death and cancer costs. Conclusions: Our novel findings suggest that suboptimal intakes of 7 dietary factors are contributing to substantial cancer burdens and healthcare costs in the US, with major additional disparities among key population subgroups. These results help inform dietary and policy priorities to reduce diet-related cancer and disparities in the US. Funding Sources: NIH/NIMHD.